Zywave(R) II 수차계로 측정한 굴절교정수술 대상안의 수술 전 안구수차 분석 - 김영승; Young Seung Kim; 고병이; Byung Yi Ko (Daihan angwa haghoi jabji, 2013)
목적: Zywave(R) II 수차계로 측정한 굴절교정수술 대상안에서의 수술 전 안구 수차의 분포에 대해 분석하고자 하였다. 대상과 방법: 116명, 232안을 대상으로 Zywave(R) II aberrometer를 이용하여 안구수차를 측정하였다. 저위수차는 구면렌즈대응치로 산출하였고, 고위수차는 6 mm 동공 지름에서, 3차에서 5차까지 총고위수차, 각 차수의 합계된 고위수차, 코마수차(Z3 -1 and Z3 1), 세조 각수차(Z3 -3 and Z3 3), 구면수차(Z4 0)의 root mean square (RMS) 값을 구하여 성별, 연령, 굴절오차(구면렌즈대응치)를 기준으로 비교 하였고, 양안의 대칭성, 중심각막두께와의 관계를 분석하였다. 결과: 평균 구면렌즈대응치는 -4.67 ± 1.83 D였으며, 총고위수차의 RMS값은 0.421 ± 0.201 μm이고, 3차, 4차 및 5차항의 합계된 RMS값은 각각 0.346 ± 0.206 μm, 0.202 ± 0.105 μm, 0.087 ± 0.048 μm이며, 코마수차, 세조각수차, 구면수차는 각각 0.241 ± 0.172 μm, 0.225 ± 0.154 μm, 0.136 ± 0.102 μm였다. 성별과 연령과는 관련성이 없었고, 굴절오차와 고위수차는 일반적으로는 관련성이 없었으나, 세조각수차는 근시 정도와 강한 상관관계를 보였다(r=-0.900, p=0.008). 양안의 차이는 없었으며, 중심각막두께와의 연관성도 보이지 않았다. 결론: Zywave(R) II 수차계로 측정한 한국인 근시안의 고위수차 분포에 대해 보고하며, 근시의 정도와 세조각수차는 상관관계가 있으며, 좌우안 대칭을 보였다. <대한안과학회지 2013;54(11):1680-1687> Purpose: To report the distribution of ocular higher-order aberrations in candidates for refractive surgery measured by Zywave(R) II aberrometer. Methods: The present study included 232 eyes of 116 subjects. Ocular aberration data were obtained by measurements per eye using Zywave(R) II aberrometer. The mean Zywave spherical equivalent (SE) and higher order aberrations (HOAs) calculated in the central 6-mm zone and expressed as root mean square (RMS) values were analyzed. Correlation analysis was performed to assess the association between ocular HOAs and gender, age, SE refractive error, or central corneal thickness (CCT) and investigate the aberration symmetry between right and left eyes. Results: The average SE was -4.67 ± 1.83 diopters (D). The mean RMS values of total HOA, 3rd, 4th or 5th summated HOAs, coma, trefoil and spherical aberration (SA) were 0.421 ± 0.201 μm, 0.346 ± 0.206 μm, 0.202 ± 0.105 μm, 0.087 ± 0.048 μm, 0.241 ± 0.172 μm, 0.225 ± 0.154 μm and 0.136 ± 0.102 μm, respectively. There was no significant differences of the mean total HOA, summated HOAs, coma, trefoil and SA between genders, age and refractive errors, but the 3rd order trefoil was strongly related with myopia (r = -0.900, p = 0.008). There was symmetry of ocular aberrations between both eyes and the ocular aberrations were not correlated with CCT. Conclusions: Herein, we report the normative distribution of ocular aberrations in the myopic Korean population measured by Zywave(R) II aberrometer. The 3rd order trefoil and myopia were correlated and mirror symmetry was observed between right and left eyes. J Korean Ophthalmol Soc 2013;54(11):1680-1687